2021
DOI: 10.1021/acsomega.0c05959
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Ca1–xEuxZrO3 as Environmentally Friendly Inorganic Yellow Pigments

Abstract: Eu 2+ -doped calcium zirconates, Ca 1−x Eu x ZrO 3 (0 ≤ x ≤ 1), were synthesized as novel environmentally friendly inorganic yellow pigments by the conventional solid-state reaction method. The crystal structure, morphology, optical properties, and color were characterized. The Eu 2+ -doped samples strongly absorbed blue light in the wavelength range of 435−480 nm, which was caused by the 4f−5d allowed transition of Eu 2+ . The color of the sample gradually became brilliant yellow with increasing the Eu 2+ con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…47,49 The substitution of Ca 2+ with La 3+ induces changes in the Ta–O/N–Ta bond angles and this may contribute to the variations in the bandgap energies of Ca 1− x La x Ta(O,N) 3 . The colour coordinate data for CaTa(O,N) 3 and Ca 0.8 La 0.2 Ta(O,N) 3 prepared in this study were compared with those reported in the literature for CaTaO 2 N synthesised by ammonolysis 26 and conventional yellow pigments such as cadmium yellow, 25 BiVO 4 20 and ZrSiO 4 :Pr 20 (Fig. 10).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…47,49 The substitution of Ca 2+ with La 3+ induces changes in the Ta–O/N–Ta bond angles and this may contribute to the variations in the bandgap energies of Ca 1− x La x Ta(O,N) 3 . The colour coordinate data for CaTa(O,N) 3 and Ca 0.8 La 0.2 Ta(O,N) 3 prepared in this study were compared with those reported in the literature for CaTaO 2 N synthesised by ammonolysis 26 and conventional yellow pigments such as cadmium yellow, 25 BiVO 4 20 and ZrSiO 4 :Pr 20 (Fig. 10).…”
Section: Resultsmentioning
confidence: 99%
“…2) prepared by urea-nitriding method in this study. Data for CaTaO 2 N prepared via the ammonolysis method 26 and commercially available yellow pigments (CdS-ZnS (cadmium yellow), 25 BiVO 4 20 and ZrSiO 4 :Pr 20 ) are also displayed for comparison.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations